(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The article considers possible risk factors affecting the health of infectious disease doctors in the course of their work, suggests solutions for health protection and improving the efficiency of infectious disease doctors. The article is devoted to the study of physical and chemical factors of the objects under study. It was revealed that in all the studied rooms the microclimate parameters were not within the established hygienic standards.